HOLISTIC EDUCATION IMAM AL-GHAZALI'S PERSPECTIVE: BUILDING LITERACY AND LEARNING MOTIVATION IN THE MODERN ERA - Friyansyah; Mahmud Arif; Muhammad Singgih; Ninik Muhajiroh (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Education has an important role in building the nation's civilization. Al-Ghazali's thinking is relevant to answer the challenges of modern education which tends to focus on the cognitive aspect, so as to forget the spiritual aspect, besides that education also functions to build literacy and motivation to learn. The research method used is library research with a qualitative approach. The results of the study show that Al-Ghazali believes that education is not only developing or improving cognitive aspects but as a means of getting closer to Allah SWT, by emphasizing the importance of intention and sincerity, the role of teachers as role models, and integration between knowledge. The integration of Al-Ghazali educational values in the modern education system can be a solution to form students who are not only intellectually intelligent, but also spiritually and morally intelligent